Effects of post-thermal annealing temperature on the optical and structural properties of gold particles on silicon suboxide films - Chan, K.; Aspanut, Z.; Goh, B.; Sow, C.; Varghese, B.; Rahman, S.A.; Muhamad, M.R. (2011)
In this work, silicon suboxide (SiOx) thin films were deposited using a RF magnetron sputtering system. A thin layer of gold (Au) with a thickness of about 10 nm was sputtered onto the surface of the deposited SiOx films prior to the thermal annealing process at 400 degrees C, 600 degrees C, 800 degrees C and 1000 degrees C. The optical and structural properties of the samples were studied using scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), X-ray diffractometry (XRD), Fourier transform infrared spectroscopy (FTIR) and optical transmission and reflection spectroscopy. SEM analyses demonstrated that the samples annealed at different temperatures produced different Au particle sizes and shapes. SiOx nanowires were found in the sample annealed at 1000 degrees C. Au particles induce the crystallinity of SiOx thin films in the post-thermal annealing process at different temperatures. These annealed samples produced silicon nanocrystallites with sizes of less than 4 nm, and the Au nanocrystallite sizes were in the range of 7-23 nm. With increased annealing temperature, the bond angle of the Si-O bond increased and the optical energy gap of the thin films decreased. The appearance of broad surface plasmon resonance absorption peaks in the region of 590-740nm was observed due to the inclusion of Au particles in the samples. The results show that the position and intensity of the surface plasmon resonance peaks can be greatly influenced by the size, shape and distribution of Au particles. (C) 2010 Elsevier B.V. All rights reserved.